Implementation of the Jarimatika Method in Grade V Mathematics Learning at Binangun State Elementary School - Pusporini, Ira Herawati Widyasari; Pangestika, Rintis Rizkia; Ngazizah, Nur Ngazizah (LPPM STKIP Kusuma Negara, 2025)
Mathematics is vital for technological and knowledge development but is often perceived as difficult and boring, reducing students' interest in learning. The objectives of this research are 1) Describe the application of jarimatika method in mathematics learning in class V of Binangun State Elementary School; 2) Knowing the average increase in student numeracy test results. This research uses a quantitative descriptive method—data collected using several stages, namely interviews, observations, tests, and documentation. The data analysis used is data reduction, data collection, and conclusion. The results of this study show that the application of the jarimatika method is beneficial for students in doing math problems, especially in multiplication so that students do not need a long time to solve the problems given by the teacher. The jarimatika method also improves the ability to count quickly but it is also seen from the increase in pre-test to post-test scores. The average score of fast counting ability of grade V elementary school students in the pre-test was 30.5% and increased to 49.4% in the post-test. The Jarimatika method is highly recommended to help students count and break the atmosphere when boredom comes into the learning process.